Integrated Management of Childhood Illness: efficiency of primary health in Northeast Brazil Atenção integrada às doenças prevalentes da infância: eficiência na atenção primária de saúde no Nordeste - Débora G Amorim; Taghreed Adam; João J F Amaral; Eleanor Gouws; Jennifer Bryce; Cesar G Victora (Universidade de São Paulo, 2008)
OBJECTIVE: The Integrated Management of Childhood Illness is a strategy designed to address major causes of child mortality. The aim of this study was to assess the impact of the strategy on the quality of child health care provided at primary facilities. METHODS: Child health quality of care and costs were compared in four states in Northeastern Brazil, in 2001. There were studied 48 health facilities considered to have had stable strategy implementation at least two years before the start of study, with 48 matched comparison facilities in the same states. A single measure of correct management of sick children was used to assess care provided to all sick children. Costs included all resources at the national, state, local and facility levels associated with child health care. RESULTS: Facilities providing strategy-based care had significantly better management of sick children at no additional cost to municipalities relative to the comparison municipalities. At strategy facilities 72% of children were correctly managed compared with 56% in comparison facilities (p=0.001). The cost per child managed correctly was US$13.20 versus US$21.05 in the strategy and comparison municipalities, respectively, after standardization for population size. CONCLUSIONS: The strategy improves the efficiency of primary facilities in Northeastern Brazil. It leads to better health outcomes at no extra cost. OBJETIVO: A atenção integrada às doenças prevalentes da infância é uma estratégia desenvolvida para contribuir na redução das principais causas de mortalidade infantil. O objetivo do estudo foi avaliar o impacto da estratégia sobre a saúde infantil. MÉTODOS: Compararam-se a qualidade do atendimento à saúde infantil e os custos associados em quatro estados da região Nordeste do Brasil, em 2001. Foram estudadas 48 unidades de saúde onde havia implementação estável da estratégia por pelo menos dois anos antes do início do estudo e 48 unidades sem (controle) nos mesmos estados. O percentual de crianças doentes atendidas corretamente foi utilizado para avaliar a qualidade da atenção oferecida a crianças doentes. O custo total da atenção à saúde infantil foi avaliado a partir de dados coletados nos níveis nacional, estadual, municipal e de unidade de saúde. RESULTADOS: As unidades que adotam a estratégia obtiveram desempenho significantemente melhor no atendimento de crianças doentes, sem custos adicionais em relação aos municípios sem. Nas unidades com a estratégia, 72% das crianças avaliadas foram atendidas corretamente, comparado com 56% nas unidades controle. O custo por criança atendida corretamente foi de US$13.20 versus US$21.05 nos municípios com e sem a estratégia respectivamente, após os ajustes para o tamanho das populações municipais. CONCLUSÕES: A estratégia melhorou a eficiência das unidades de atenção primária de saúde da região estudada. Em unidades de atenção primária com a estratégia, a qualidade do tratamento foi melhor, sem aumento de custos.